Pop sorghum - Visarada, KBRS; Aruna, C; Elangovan, M; Jacob, Jinu; Ratnavathi, C (Indian Farming, 2023)
Sorghum is a multipurpose crop and its use as food is the key component. Rotis and cooked sorghum are primary consumption patterns, while there are other foods and snacks locally popular in India. One such delicacy is the sorghum pops, as described in this article. Popped sorghum is easy for digestion and is used as weaning food. Sorghum pops are traditionally made with elaborateprocedure of soaking, shade drying and popping in pans. In this article, sorghum popping was tested using popcorn maker, a small device that can be purchased with a low cost. The advantage of this procedure is that this pop-maker can be used to pop a handful of seeds and it takes 2–3 min only for the same. It can be explored as an additional income source. There are many varieties releasedfor popping, e.g. Phule Panchami (RPOSV-3), Pop11 and other lines in pop series. Advanced lines having high popping and high yield through breeding efforts are in the pipeline.